Digital China: from cultural presence to innovative nation - Keane, Michael; Chen, Y. (2017)
The rapid development of digital technology infrastructure in the People’s Republic of China, together with the government’s recent support of grassroots innovation, has led to a growing mood of techno-nationalism as well as a feeling that digital technology can play an important role in renovating China’s international image. Powerful internet companies are challenging the dominance of traditional state-owned media. Cultural products are digitized, distributed, and consumed on online platforms. Such platforms offer consumers a choice of content through subscription, either free or paid. With China’s media and culture striving to ‘go out’ (zou chuqu 走出去), typified by CCTV and Confucius Institutes, we pose the question: Can China use the ‘digital power’ of the internet to achieve international recognition as an ‘innovative nation’ or will the internet perpetuate a stereotype of China as a copycat nation?